Transforming Early Childhood Education through Digital Play and Interactive Flat Panels - Nur Aisyah; Fatimatuz Zahro (Program Studi Pendidikan Agama Islam, Fakultas Tarbiyah, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2025)
This study explores the implementation of technology-enhanced Play-Based Learning (PBL) through the use of Interactive Flat Panels (IFPs) in an early childhood education context. Adopting a qualitative case study design at TK Masyithoh Mambaul Ulum Paiton, data were collected through classroom observations, semi-structured interviews with teachers and parents, and analysis of instructional documentation. The study examines how digital pedagogy is enacted within play activities and how such practices relate to holistic child development. Findings suggest that PBL was deliberately structured by aligning developmental objectives with integrated concrete, role-based, and digital play scenarios. The incorporation of IFP technology appeared to influence patterns of classroom engagement, particularly in children’s attentional focus and collaborative interaction. Observational data indicate that language and social-emotional domains were more prominently stimulated, while fine motor and analytical domains received comparatively less emphasis. Rather than asserting causal effectiveness, this study provides a context-sensitive account of how digital tools are pedagogically interpreted and integrated within play-based instruction. The findings underscore the importance of teacher readiness and intentional design in shaping balanced developmental stimulation. This case contributes to ongoing discussions on digital pedagogy in early childhood education by highlighting the complexities of integrating interactive technology within a holistic Play-Based Learning framework.